KINERJA DAN KOEFISIEN KERAGAMAN SIFAT-SIFAT PRODUKSI KAMBING PERANAKAN ETTAWA (PE) DI KABUPATEN JEMBRANA, PROVINSI BALI - D. A., WARMADEWI; BIDURA, I. G. N. G.; BUDIANA, I. N.; MELATI, N. P. Y. (Majalah Ilmiah Peternakan, 2023)
The selection program is an effective effort to improve the genetic quality of livestock, if the population of the selected livestock has a trait with high phenotypic diversity. The amount of phenotypic diversity of the population is measured by calculating the coefficient of variation (CV). A population is said to be diverse if the CV value is >15%. This study aims to examine the performance and coefficient of variability of PE goat production traits in Jembra- na Regency, Bali Province. The study was conducted for 6 months on livestock groups in Jembrana Regency, Bali Province, by measuring the performance of production characteristics (shoulder height, body length, chest circum- ference, ear length, and body weight) of female PE goats. Furthermore, the measurement results were grouped by tooth (I0; I1; and I2). Data analysis was carried out descriptively to obtain the average characteristics of PE goat production and calculate the CV value. The results showed that the performance of female PE goats in the age group I0; I1; and I2 is higher than the Indonesian National Standard (SNI 7352.1:2015), regarding Ettawa Crossbreed go- ats. The CV values for the production characteristics of female PE goats in the I0 age group were more diverse than those in the I1 and I2 age groups. It can be concluded that to obtain superior breeds of PE goats according to SNI 7352.1:2015 concerning Ettawa Crossbreed goats, the selection can be made starting at the age group I0.